Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.21273/hortsci11226-16
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Tillage Impacts on Pumpkin Yield, Weed Pressure, Soil Moisture, and Soil Erosion

Abstract: Conservation tillage has the potential to decrease the environmental footprint of pumpkin production, but possible trade-offs with yield are not well understood. This study experimentally tested the effects of three cultivation techniques (conventional-till, strip-till, and no-till) on pumpkin production, weed pressure, soil moisture, and soil erosion. Randomized complete block field experiments were conducted on Cucurbita pepo L. ‘Gladiator’ pumpkins in 2014 and 2015. Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…CA can also reduce erosion (Mafongoya et al, 2016) and may be adaptive in areas that experience increased incidence of heavy precipitation (Figure 2). Indeed, fields in which pumpkins were being grown under CA lost nine times less soil than conventional plots during a simulated storm event, without sacrificing yields (O’Rourke and Petersen, 2016). No‐till practices can also increase soil organic carbon (Lee et al, 2019) and reduce methane emissions compared to conventional tillage, providing potential climate change mitigation benefits (Somasundaram et al, 2020).…”
Section: Implications For Ecological Weed Managementmentioning
confidence: 99%
“…CA can also reduce erosion (Mafongoya et al, 2016) and may be adaptive in areas that experience increased incidence of heavy precipitation (Figure 2). Indeed, fields in which pumpkins were being grown under CA lost nine times less soil than conventional plots during a simulated storm event, without sacrificing yields (O’Rourke and Petersen, 2016). No‐till practices can also increase soil organic carbon (Lee et al, 2019) and reduce methane emissions compared to conventional tillage, providing potential climate change mitigation benefits (Somasundaram et al, 2020).…”
Section: Implications For Ecological Weed Managementmentioning
confidence: 99%
“…However, other research even demonstrated increased erosion rates of 47 t ha −1 year −1 (Vanwalleghem et al, 2011). In cropland vegetable fields, soils also exceed very often tolerable soil loss (Montgomery, 2007), reaching 12 t ha -1 year -1 (Bagarello et al, 2018;O'Rourke and Petersen, 2016;Pournader et al, 2018;Preiti et al, 2017). In this context, the preservation management strategies developed in the shape of no-tillage (croplands), grass cover (orchards), or mulching (croplands and orchards) (Triplett and Dick, 2008) are key to conserve the soils.…”
Section: Introductionmentioning
confidence: 99%
“…Ornamental jack-o-lantern-type pumpkins are a widely grown specialty crop that will generally produce similar yields between notill (NT) and conventional till (CT) production systems (Harrelson et al, 2007;O'Rourke and Petersen, 2016;Walters, 2016;Walters and Young, 2010). In recent years, NT practices have become more prominent in Midwest pumpkin production systems as a result of growers having gained more understanding of the economic and ecological benefits associated with this type of production system (Walters, 2016(Walters, , 2019.…”
mentioning
confidence: 99%